Characterization of maize producing households in the dry savanna of Mali - Fofana, M.; Abdoulaye, Tahirou; Coulibaly, N.; Sanogo, D.; Langyintuo, A. (International Institute of Tropical Agriculture, 2011)
Maize is one of the three most important staple foods in Mali. Zones in the country with high potential for producing maize are limited to areas where the probability of drought risk is between 20 and 40%, meaning that recurring droughts have long handicapped maize production. In an attempt to alleviate drought stress on maize production, a household survey was conducted in the two Local Government Areas of Bougouni and Koutiala, both in the Sikasso Region, during the 2007/2008 production period. These two districts were selected following an environmental characterization of drought zones in Mali. The survey was mainly oriented towards maize based farming systems. Six sample villages were selected within each of the two districts. The sample population was defined as maize farming households. A total of 150 households were randomly selected and interviewed with structured questionnaires. Interviews were conducted by trained enumerators using a formal household survey. The purpose of the study is to provide both quantitative and qualitative feedback from farmers to researchers and to the B&MGF on the impact that improved maize varieties developed in the past have had upon the livelihoods of households and to provide a detailed database for the projection of expected outcomes with the deployment of new drought tolerant maize varieties under the B&MGF drought tolerant maize project. Both qualitative and quantitative analyses were used to extract from our set of variables those orthogonal linear combinations of the variables that best captured the common information. Most successful was the one proposed by Filmer and Pritchett (1998; 2001) called the Principal Component Analysis (PCA). To assess the variables affecting the adoption of improved maize varieties, the Tobit model was used. The results show that 99% of household heads are male. The size of a household is 22 persons, on average. About 47% of the household’s members are available for farm work. About 59% of household heads are illiterate, an important factor concerning the adoption of new technology. These household heads make decisions about 84% of farming activities; 86% of the households involved in the study belonged to at least one farmers’ organization in order to have easy access to inputs.